2015
DOI: 10.1089/cell.2015.0049
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Bone Morphogenetic Protein 6 Enhances Oocyte Reprogramming Potential and Subsequent Development of the Cloned Yak Embryos

Abstract: This study investigated the effects of bone morphogenetic protein 6 (BMP6) supplementation in the medium during in vitro maturation (IVM) on the developmental potential of oocytes and in the subsequent development of cloned yak embryos. Cumulus-oocyte complexes (COCs) were aspirated from the antral follicles of yak ovaries and cultured with different concentrations of recombinant human BMP6 in oocyte maturation medium. Following maturation, the metaphase II (MII) oocytes were used for somatic cell nuclear tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…We also observed that the level of H3K9me3 in the C-NT group was significantly higher than that in the IVF group at the 2PN and two-cell stages. This finding is consistent with the previous finding in cloned bovine embryos (Pan, He et al 2015),…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We also observed that the level of H3K9me3 in the C-NT group was significantly higher than that in the IVF group at the 2PN and two-cell stages. This finding is consistent with the previous finding in cloned bovine embryos (Pan, He et al 2015),…”
Section: Discussionsupporting
confidence: 94%
“…These epigenetic markers on chromatin were thought to be at the core of genome reprograming after fertilization or SCNT (Zhao, Whyte et al 2010). To clarify the underlying mechanisms, we focused on the expression level of H3K9me3, which is associated with the repression of chromatin, and the formation of heterochromatin (Pan, He et al 2015). Our data showed that H3K9me3 was detected only in female pronuclei during the pronuclear period in IVF embryos.…”
Section: Discussionmentioning
confidence: 88%
“…BMP6, part of the TGF-β superfamily, plays a critical role in ovarian function and fertility through bidirectional communication between granulosa cells and oocytes [38]. To date, very few studies have investigated effects of BMP6 on mammalian oocytes and embryos; however, recent research demonstrated that treatment of the culture medium with BMP6 enhanced the maturation rate of oocytes and developmental competence of embryos [39]. We demonstrated that BMP6 expression was markedly increased in CCs and OOs derived from the estrus stage, while OCs showed significantly high gene expression of BMP6 in the diestrus stage.…”
Section: Discussionmentioning
confidence: 99%
“…Immature COCs were washed three times with tissue culture medium, consisting of TCM‐199 (Gibco B.R.L. ), 50 μg/ml gentamicin, 200 mM pyruvate, 1 μg/ml β‐oestradiol (E2), 100 μg/ml follicle‐stimulating hormone (FSH) and 10% FBS (Pan, He, et al., 2015). Then, the COCs were randomly divided into four groups, and approximately 40–50 COCs were cultured in 400 µl of IVM medium in four‐well dishes (Nunc, Roskilde, Denmark) and cultured with mineral oil overlay.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence staining was described previously (Pan, He, et al., 2015; Wen et al., 2017) with some modifications. Briefly, different groups of COCs were fixed in PBS with 4% paraformaldehyde for 1 h at RT, and COCs were washed 3 times with PBS containing 2% BSA.…”
Section: Methodsmentioning
confidence: 99%